Bundled Payments in Total Joint Replacement: Keeping Our Care Affordable and High in Quality - McLawhorn, Alexander S. (Curr Rev Musculoskelet Med, 2017)
PURPOSE OF REVIEW: The purpose of this review was to evaluate the literature regarding bundle payment reimbursement models for total joint arthroplasty (TJA). RECENT FINDINGS: From an economic standpoint, TJA are cost-effective, but they represent a substantial expense to the Centers for Medicare & Medicaid Services (CMS). Historically, fee-for-service payment models resulted in highly variable cost and quality. CMS introduced Bundled Payments for Care Improvement (BPCI) in 2012 and subsequently the Comprehensive Care for Joint Replacement (CJR) reimbursement model in 2016 to improve the value of TJA from the perspectives of both CMS and patients, by improving quality via cost control. SUMMARY: Early results of bundled payments are promising, but preserving access to care for patients with high comorbidity burdens and those requiring more complex care is a lingering concern. Hospitals, regardless of current participation in bundled payments, should develop care pathways for TJA to maximize efficiency and patient safety.